Eurasian Economic Union creates innovation and intellectual opportunities for social and economic development of the country - Shedenov, U. K. (Journal of Economic Research & Business Administration, 2016)
Eurasian Economic Union, for our countries a source of new opportunities such as the development of international cooperation, diversification of foreign policy, development of the national economic and commercial interests. The future of our country - its intellectual resources, science and innovation achievements. The whole experience of developed countries shows that the economic development and prosperity - to be a leader in the area of scientific and technological innovation. Thus, learn foreign technologies and equipment, and also makes it possible for the development of national scientific and technological capacity to implement in the production of scientific achievements of domestic production, and the need to appreciate them. One of the main purposes of creating the Eurasian Economic Union, to combine the capabilities of each country in order to jointly develop the economy and to strengthen competitiveness.